Investigation of the Direct Methanol Fuel Cell with Novel Assembly Method. Issue 5 (10th June 2013) - Yuan, Z. Y.; Zhang, Y. F.; Fu, W. T.; Li, Z. P.; Liu, X. W.
Abstract Assembly pressure compresses the under part of the gas diffusion layer, and the inhomogeneous compression can cause performance variation of the direct methanol fuel cell. Compared with the cell with traditional assembly method using bolts at the corner of plates, the cell with a novel assembly method uniforming the pressure is designed, fabricated, and tested in this paper. First, a three‐dimensional model is developed to simulate the pressure distribution with different assembly patterns. Then, a multi‐physics simulation including methanol mass transport, methanol diffusion, and electron transport is conduced. The modeling results reveal that the novel assembly method can ensure the flatness of the membrane electrode when compared with the traditional method. The overall performance first increases and then decreases with the increase of assembly pressure, and the optimal pressure is 1.5 MPa. Additionally, the cell with both assembly methods are fabricated and tested under optimal condition, and there are only <8% discrepancy between the experimental results and simulation; Influences of cell efficiency patterned with two assembly methods are also studied.